2009
DOI: 10.1029/2008jc005201
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of scatterometer‐derived wind fields in the north Indian Ocean with a data‐adaptive approach

Abstract: A combination of genetic algorithm (GA) and empirical orthogonal function (EOF) analysis has been employed to forecast satellite scatterometer–observed surface winds in the north Indian Ocean. The EOFs are used to compress the major part of the spatial variability into a few eigenmodes. The temporal variability is contained in the corresponding principal components (PC) which have been subjected to singular spectrum analysis for filtering out the random part. Forecast of the deterministic part has been carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Thus it is ideal for those scientists, for example, scientists involved in crop forecast modeling, who only require forecasts of certain Agro-Met parameters at isolated locations, representative of a small area. The shortcoming is of course that it is not easy to generalize this algorithm for predicting weather parameters over the entire globe, or over large threedimensional regions, although there are promising twodimensional generalizations [5,6,[8][9][10]15]. The method is highly suitable for location-specific forecasts as demonstrated in the present study.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus it is ideal for those scientists, for example, scientists involved in crop forecast modeling, who only require forecasts of certain Agro-Met parameters at isolated locations, representative of a small area. The shortcoming is of course that it is not easy to generalize this algorithm for predicting weather parameters over the entire globe, or over large threedimensional regions, although there are promising twodimensional generalizations [5,6,[8][9][10]15]. The method is highly suitable for location-specific forecasts as demonstrated in the present study.…”
Section: Resultsmentioning
confidence: 86%
“…(GA). The algorithm has been discussed in detail by several authors [1,2,9,15]. However, for the benefit of the present readers, we describe below the essential details of the algorithm, borrowing heavily from the reference [15].…”
Section: Agro-met Station (Ams) Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The EOF analysis is earlier used by Jones et al (1995) and Rao et al (2002) over the Indian Ocean to understand the variability of surface fluxes and wind stress curl. Recent studies of Sharma et al (2007a, b) and Basu et al (2009) have demonstrated wind forecast techniques using EOF analysis in conjunction with genetic algorithm on satellite scatterometer derived winds for the AS, BOB and north Indian Ocean regions separately. However, to the best of the knowledge and belief of the present authors, no study has been reported in the literature so far on the variability of the SWH using EOF in the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Basu et al have taken use of a combination of genetic algorithmand EOF analysis to forecast satellite scatterometer observed surface winds in the north Indian Ocean[27].…”
mentioning
confidence: 99%